La hermenéutica analógica y sus ámbitos (2021)
This article shows some views related to analogical hermeneutics as a theory of interpretation in which the equivocity and univocity ends are avoided. Under this scenario it is of vital importance to take a historical journey through the notions of analogy and hermeneutics in order to show the relevance of this study. Above all, the aim is to avoid the polarizations that lead philosophy into undesirable grounds. Instead, a balance between absolutist exactitudes and complete ambiguity is sought.